Posterior cloaca: Multicenter experience of a very rare and unusual anorectal and genitourinary malformation - Rohit Kapoor; Amit Gupta; Partap Singh Yadav; Ankur Mandelia (Wolters Kluwer Medknow Publications, 2022)
Aim: Posterior cloacal malformations (PCMs) are distinguished from classical cloacal malformations by the posterior location of the common opening in the perineum. We aim to describe our experience of management of these rare and complex malformations. Methods: This study was a retrospective chart review of all patients with PCM who underwent treatment at Kalawati Saran Children's Hospital (KSCH), New Delhi, and Sanjay Gandhi Postgraduate Institute of Medical Sciences (SGPGIMS), Lucknow, between 2013 and 2021. Individual anatomical variations and their impact on the clinical presentation, management, and final outcome (cosmesis and function) were recorded and analyzed. Results: During the study period, four girls with a median age of 2 (range: 0-5) years presented to us with PCM. Three patients were referred to KSCH as ambiguous genitalia whereas one patient was born at SGPGIMS with an antenatal diagnosis of "urorectal septal defect." On examination, three patients had the urogenital sinus (UGS) opening immediately anterior to the normally located anal opening (2 orifices), whereas one had a single orifice at the normal location of the anus with the UGS opening in the anterior rectal wall. Associated anomalies included: (a) hydrocolpos (n = 3), which was managed by a tube vaginostomy; (b) urethral duplication with dorsal atretic urethra (n = 3); (c) uterine didelphys (n = 1); (d) bilateral grade 5 vesicoureteric reflux (n = 1); and (e) vaginal calculus (n = 1). Total urogenital mobilization (anterior sagittal approach) with feminizing genitoplasty was performed for patients with UGS and normal anus (n = 3). In the patient with a single opening at the normal location of the anus, posterior sagittal ano-recto-urethro-vaginoplasty was performed. At a median follow-up of 24 months, three patients are continent for urine and stool, whereas one patient is yet to be toilet trained. Conclusions: PCMs are unusual complex malformations that necessitate meticulous clinical examination, detailed diagnostic workup, and multistaged surgical management. Management should be tailored as per each individual patient's anatomy and clinical presentation for an optimal outcome.